Dynamics and nature of support in the personal networks of people with type 2 diabetes living in Europe: qualitative analysis of network properties. (13th November 2014) - Kennedy, Anne; Rogers, Anne; Vassilev, Ivaylo; Todorova, Elka; Roukova, Poli; Foss, Christina; Knutsen, Ingrid; Portillo, Mari Carmen; Mujika, Agurtzane; Serrano‐Gil, Manuel; Lionis, Christos; Angelaki, Agapi; et al.
Abstract: Background: Living with and self‐managing a long‐term condition implicates a diversity of networked relationships. This qualitative study examines the personal communities of support of people with type 2 diabetes. Methods: We conducted 170 biographical interviews in six European countries (Bulgaria, Greece, the Netherlands, Norway, Spain and UK) to explore social support and networks. Analysis was framed with reference to three predetermined social support mechanisms: the negotiation of support enabling engagement with healthy practices, navigation to sources of support and collective efficacy . Each interview was summarized to describe navigation and negotiation of participants' networks and the degree of collective efficacy. Results: Analysis highlighted the similarities and differences between countries and provided insights into capacities of networks to support self‐management. The network support mechanisms were identified in all interviews, and losses and gains in networks impacted on diabetes management. There were contextual differences between countries, most notably the impact of financial austerity on network dynamics. Four types of network are suggested: generative, diverse and beneficial to individuals; proxy, network members undertook diabetes management work; avoidant, support not engaged with; and struggling, diabetes management a struggle or not prioritized. Conclusions: It is possible to differentiate types of network input to living with and managing diabetes. Recognizing the nature of active, generative aspects of networks support is likely to have relevance for self‐management support interventions either through encouraging continuing development and maintenance of these contacts or intervening to address struggling networks through introducing the means to connect people to additional sources of support.